An Overview of the Blue Gene/L System Software Organization - Almasi, George; Bellofatto, Ralph; Brunheroto, José; Caşcaval, Călin; Castaños, José G.; Ceze, Luís; Crumley, Paul; Erway, C. Christopher; Gagliano, Joseph; Lieber, Derek; Moreira, José E.; Sanomiya, Alda; et al. (EuroPar 2003 (International Conference on Parallel and Distributed Computing), 2003)
The Blue Gene/L supercomputer will use system-on-a-chip integration and a highly scalable cellular architecture to deliver 360 Teraflops of peak computing power.With 65,536 compute nodes, Blue Gene/L represents a new level of scalability for parallel system, with specific challenges in the areas of scalability, maintenance and usability. In this paper we present our vision of a software architecture that faces up to these challenges, and a simulation framework that we have used to experiment with our ideas.
Distinguished paper - also published in Parallel Processing Letters, Vol.13, Number 4, December 2003